2020
DOI: 10.15421/2020_205
|View full text |Cite
|
Sign up to set email alerts
|

Using of Taraxacum officinale (L.) pollens for the urban park bioindication

Abstract: Palinoindication of 6 parks of the urban ecosystem of Kiev using Taraxacum officinale (L.) Weber ex F.H. Wigg. population, was carried out. There is a general trend towards an increase in the amount of nonviable pollen with an increase in anthropogenic load. In the example of T. officinale, this is manifested in a gradual increase to 27% of non-viable pollen on the pollution gradient. With the deterioration of the ecological situation in the studied test polygons, an increase in the number of teratomorphic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…We also observed similar processes. We studied the correlations between the parameters of pollen indication in Kyiv (Mazura et al 2020), but now, it is found that compared to studies in 2013 (Kudryavska and Dychko 2013), there has been a deterioration of the environmental situation in the integrated indicator of CID by 19.3% for 7 years. We have shown that there is a process of nitrification in PEs with excess nitrogen from the emissions of vehicles through phytoindication (Miroshnyk 2020).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We also observed similar processes. We studied the correlations between the parameters of pollen indication in Kyiv (Mazura et al 2020), but now, it is found that compared to studies in 2013 (Kudryavska and Dychko 2013), there has been a deterioration of the environmental situation in the integrated indicator of CID by 19.3% for 7 years. We have shown that there is a process of nitrification in PEs with excess nitrogen from the emissions of vehicles through phytoindication (Miroshnyk 2020).…”
Section: Discussionmentioning
confidence: 97%
“…In Europe, North America and China, tree species, herbaceous, including Taraxacum officinale Web., are used as indicators of the state of urban environ-ment (Leghari et al 2018;Martines 2018;Zajecka and Świercz 2021). In studies of the impact of air pollutants and heavy metals on the environment, various plant indicators are used, in particular, palynoindication (Cuinica et al 2014(Cuinica et al , 2015Ivanchenko and Bessonova 2016;Leghari et al 2018;Petrushkevych and Korshykov 2020;Mazura et al 2020;Bessonova and Sklyarenko 2020), life status of plantations (Nock et al 2013;Vieira et al 2018;Rybakova and Glazunov 2020;Vacek et al 2020;Jaung et al 2020), the level of defoliation of the crown (Vacek et al 2020;Miroshnyk 2018), leaf damage (chlorosis-necrosis) (Miroshnyk 2018; Pietras-Couffignal and Robakowski 2019), changes in anatomy, content and ratio of photosynthetic pigments (Ivanchenko and Bessonova 2016;Suskalo 2018), enzymes (Suskalo 2018) and other physiological processes. The correlation between the concentrations of NO x , SO 2 and the number of passing cars and defoliation of trees (Vacek et al 2020) have been established.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Запропоновано систему показників для експресдіагностики стану зелених насаджень у межах мегаполісу 10 . Проведено паліноіндикацію паркових екосистем (ПЕ) Києва та екологічне зонування території з урахуванням ролі збережених природних екосистем [11,12].…”
unclassified